EVALUASI KINERJA STRUKTUR BANGUNAN MENGGUNAKAN PUSHOVER ANALYSIS DENGAN METODE ATC-40 DAN FEMA 356 - R. Hendarto Prasetyo R. Bambang Kusuma Prihadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2020)
Pushover analysis is a non-linear static analysis to determine the collapse behavior of a building or structure. The analysis is carried out by giving a static lateral load pattern to the structure, which is then gradually increased by a multiplier until a buliding movement target is reached. This final assignment research was conducted to determine the performance point based on ATC-40, to determine the performance level based on ATC-40, and to determine the performance level based on FEMA 356. The research method used the response spectrum with the SAP2000 v14 program. The result of the performance point in building with the values of Sa = 0,737, and Sd = 0,200 for the push X, while the values of push Y Sa = 0,680, and Sd = 0,225. The calculation of ATC-40 in building shows the value of the drift ratio in the X direction 0,01165 and the drift ratio Y direction 0,0127 at the level of performance Immediate Occupancy (IO). The result of FEMA 356 calculation in building shows the value of the lateral displacement target structure of the X direction structure = 0,00437 (0,437 %), and the value of the lateral displacement target of the Y direction structure = 0,006 (0,6 %) and at the level of performance Immediate Occupancy (IO). Then it could be concluded that The Dental & Mouth Hospital of UGM Prof. Soedomo, was at the level of performance Immediate Occupancy (IO), meaning that the building was still safe and could be reused after the earthquake and don’t occured serious demage.